The Global Governance Divide: How Major Jurisdictions are Regulating AI for a Safer Future - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The Global Governance Divide: How Major Jurisdictions are Regulating AI for a Safer Future The rapid proliferation of Artificial Intelligence (AI) acros...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning